New mediation practices in African conflicts (Ulf Engel) (The Strategic Review for Southern Africa, 2020)
This volume is the result of the editor's fellowship at the Wallenberg Research Centre of the Stellenbosch Institute of Advanced Studies, which ended with an international workshop on the subject, held in September 2011. The contributions engage from different angles and perspectives with a wider range of case studies and thematic issues observing trends and ongoing shifts in African security architecture and subsequent approaches to and practices of intervention by mediation. As the editor  observes: "These efforts are related to a larger process of norm change, including a new preference for non-indifference as opposed to non interference in each other's affairs and an emphasis on human security as opposed to traditional regime security" (p 2).
Keywords: African security architecture; Engel, Ulf; New Mediation Practices in African Conflicts; traditional regime security